A Survey on Wireless Malevolent Access Point Detection Methods for WLAN - Rajput, Punam; Kulkarni, Prasad (International Journal of Computer Sciences and Engineering, 2025)
In Current Trends many public places like bus stations, restaurant, malls etc. provides Wi-Fi connectivity to the users with free of cost. These public places having a device like wireless access point through which they provide service to the end users. . It is designed to utilize the existing wireless LAN infrastructure. These rogue access points (APs) expose the enterprise network to a barrage of security vulnerabilities in that they are typically connected to a network port behind the firewall. The growing acceptance of wireless local area network causes a risk of wireless security attacks. The attacker creates a malevolent access point to attract the users and perform attacks on user devices through WLAN. Malevolent access point is one of the serious threats in wireless local area network. We Study in this paper survey on recent different fake access point detection methods and identified their advantages and disadvantages.